Efficacy of Tranexamic Acid in Reducing Seroma and Hematoma Formation Following Reduction Mammaplasty. (20th November 2021) - Weissler, Jason M; Kuruoglu, Doga; Antezana, Luis; Curiel, Daniel; Kerivan, Lauren; Alsayed, Ahmed; Banuelos, Joseph; Harless, Christin A; Sharaf, Basel A; Vijayasekaran, Aparna; Martinez-Jorge, Jorys; Tran, Nho V; et al.
Abstract: Background: Tranexamic acid (TXA) has gained increasing recognition as a valuable pharmacologic agent within plastic surgery. Objectives: The aim of this study was to investigate the value and safety profile of both intravenous and topically administered TXA in the setting of bilateral reduction mammaplasty. Methods: A retrospective review was performed to identify consecutive patients who underwent bilateral reduction mammaplasty for symptomatic macromastia (January 2016-July 2021). Pertinent preoperative, intraoperative, and postoperative details were collected/reviewed. Primary outcome measures included hematoma requiring surgical evacuation and clinically significant/symptomatic seroma formation mandating percutaneous aspiration. Patients taking anticoagulation/antiplatelet medication or those with a history of thromboembolic diseases were excluded. Patients who had received TXA were compared to a historical control group who did not receive TXA within the same consecutive cohort. Results: A total of 385 consecutive patients (770 breasts) were included. TXA was used in 514 (66.8%) cases (topical, 318 [61.9%]; intravenous, 170 [33.1%]; intravenous and topical, 26 [5.1%]). Neither seroma nor hematoma were impacted/reduced with TXA ( P > 0.05). Increased age (hazards ratio, 1.06 per 1-year increase; 95% CI, 1.004-1.118) significantly increased the risk of hematoma ( P = 0.032). The use of drains significantly decreased the risk of seroma ( P < 0.0001). Increased BMI increased the risk of seroma (hazards ratio, 1.16 per 1-kg/m 2 increase; 95% CI, 1.06-1.26; P = 0.0013). The use of TXA did not impact drain duration. Conclusions: This study, the largest to date on the use of IV and topical TXA, did not find any reduction in risk when using TXA in breast reduction surgery. Level of Evidence: 3: